High-performance Fuel Cell with Stretched Catalyst-Coated Membrane: One-step Formation of Cracked Electrode - Kim, Sang Moon (Sci Rep, 2016)
We have achieved performance enhancement of polymer electrolyte membrane fuel cell (PEMFC) though crack generation on its electrodes. It is the first attempt to enhance the performance of PEMFC by using cracks which are generally considered as defects. The pre-defined, cracked electrode was generated by stretching a catalyst-coated Nafion membrane. With the strain-stress property of the membrane that is unique in the aspect of plastic deformation, membrane electrolyte assembly (MEA) was successfully incorporated into the fuel cell. Cracked electrodes with the variation of strain were investigated and electrochemically evaluated. Remarkably, mechanical stretching of catalyst-coated Nafion membrane led to a decrease in membrane resistance and an improvement in mass transport, which resulted in enhanced device performance.